HUBUNGAN PERSONAL HYGIENE DENGAN KEJADIAN KEPUTIHAN PADA REMAJA PEREMPUAN - Dini Erlisa Adhani; Dwi Agustin; Melinda Asturia; Wahyudi (PT. Saha Kreasi Indonesia, 2025)
Vaginal discharge is a common problem in adolescent girls and can be influenced by various factors, including personal hygiene practices. Daily hygiene practices, such as vulvar cleaning, bathing frequency, underwear selection, and sanitary pad use, play a role in preventing infection and maintaining reproductive health. Although numerous studies have discussed vaginal discharge and its risk factors in general, the specific relationship between personal hygiene and the occurrence of vaginal discharge in adolescent girls still requires specific review. to determine the relationship between personal hygiene and the incidence of vaginal discharge in adolescent girls This article uses a literature review method by examining various national and international journals, reports from the WHO, CDC, and BKKBN, and related research. The literature was selected based on its recency (last 5 years), relevance, and publisher credibility. Searches were conducted through Google Scholar, PubMed, and DOAJ databases using the keywords